A Study Skills Handbook - Smith, Mike, 1945 June 7-.; Smith, Glenda (Oxford : Oxford University Press, 1990)
A clear presentation of the various skills required for study at university level, this text includes many exercises that practice the following: using dictionaries, reading, note-taking, using university libraries and examination procedures.
Previous ed.: 1988.
Bibliography: p219-220. - Includes index.